2018
DOI: 10.1038/s41598-018-21720-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced long non-coding RNA Malat1 is dispensable for renal ischemia/reperfusion-injury

Abstract: Renal ischemia-reperfusion (I/R) injury is a major cause of acute kidney injury (AKI). Non-coding RNAs are crucially involved in its pathophysiology. We identified hypoxia-induced long non-coding RNA Malat1 (Metastasis Associated Lung Adenocarcinoma Transcript 1) to be upregulated in renal I/R injury. We here elucidated the functional role of Malat1 in vitro and its potential contribution to kidney injury in vivo. Malat1 was upregulated in kidney biopsies and plasma of patients with AKI, in murine hypoxic kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 33 publications
4
55
0
Order By: Relevance
“…However, in 2012, Eissmann et al [23], Nakagawa et al [25], and Zhang et al [46] independently generated Malat1 knockout mice and found the homozygous knockouts to be viable and fertile, with no obvious phenotypes or histological abnormalities, including no obvious defects in nuclear speckles where this lncRNA localizes. Furthermore, despite significant evidence of involvement of Malat1 in hypoxia response and specifically in renal ischemia-reperfusion injury, no discernable in vivo effect of the lncRNA on that condition was observed in a mouse knockout [24]. On the other hand, in vivo effect of Malat1 in brain tissues after ischemic stroke could be observed; however, no RNA rescue experiments have been conducted in those studies [48] (also see below for additional discussion of Malat1 in vivo studies).…”
Section: Lncrnas Appear To Be Dispensable For a Vertebrate Organismmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in 2012, Eissmann et al [23], Nakagawa et al [25], and Zhang et al [46] independently generated Malat1 knockout mice and found the homozygous knockouts to be viable and fertile, with no obvious phenotypes or histological abnormalities, including no obvious defects in nuclear speckles where this lncRNA localizes. Furthermore, despite significant evidence of involvement of Malat1 in hypoxia response and specifically in renal ischemia-reperfusion injury, no discernable in vivo effect of the lncRNA on that condition was observed in a mouse knockout [24]. On the other hand, in vivo effect of Malat1 in brain tissues after ischemic stroke could be observed; however, no RNA rescue experiments have been conducted in those studies [48] (also see below for additional discussion of Malat1 in vivo studies).…”
Section: Lncrnas Appear To Be Dispensable For a Vertebrate Organismmentioning
confidence: 99%
“…One side in this debate argues that most of the currently annotated lncRNAs are not functional and represent spurious byproducts of mRNA biogenesis, leaky transcription, or other processes that confer no fitness advantage [16][17][18][19][20]. Consistent with these views, recent in vivo studies with knockouts of multiple lncRNAs reported no observable phenotypes [21][22][23][24][25][26][27][28][29][30][31]. Moreover, the biological functions of lncRNAs observed in different studies are often controversial, even with regard to some transcripts that are considered as the "gold standards" by the community (see below for details).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has indicated the significant roles of lncRNAs in the pathophysiology of AKI, and the crosstalk between lncRNA and AKI has been widely reported in recent years [18][19][20]. LncRNAs are involved in the progression of AKI by regulating many important factors.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has suggested that lncRNAs regulate these pathological processes in renal injury. The lncRNAs MALAT1, TapSAKI, and PVT1 were the most reported lncRNAs involved in the pathogenesis of acute renal injury in humans by modulating inflammation, cell death, and survival [22][23][24]. However, due to the lack of extensive research, the role of lncRNAs in renal IR injury is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%